2022
DOI: 10.1111/ajt.16807
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a simple web-based tool for early prediction of COVID-19-associated death in kidney transplant recipients

Abstract: This analysis, using data from the Brazilian kidney transplant (KT) COVID‐19 study, seeks to develop a prediction score to assist in COVID‐19 risk stratification in KT recipients. In this study, 1379 patients (35 sites) were enrolled, and a machine learning approach was used to fit models in a derivation cohort. A reduced Elastic Net model was selected, and the accuracy to predict the 28‐day fatality after the COVID‐19 diagnosis, assessed by the area under the ROC curve (AUC‐ROC), was confirmed in a validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 60 publications
0
20
0
4
Order By: Relevance
“…As expected, several patient characteristics have an impact on the serological response after vaccination: older patients, more recently grafted patients, and those with poorer kidney graft function are at a higher risk of non-response. Age and lower GFR were also predictive of fatal outcomes in a Brazilian cohort used to establish a tool for the early prediction of COVID-19-associated death after kidney transplantation [ 26 ], and immunosenescence likely played a role in both observations [ 27 ]. Beyond patient age, the intensity of early immunosuppression with high rates of triple immunosuppression, higher MPA exposure, higher CNI trough levels, and various induction regimens with monoclonal or polyclonal antibodies (data not shown) favored non-response to vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, several patient characteristics have an impact on the serological response after vaccination: older patients, more recently grafted patients, and those with poorer kidney graft function are at a higher risk of non-response. Age and lower GFR were also predictive of fatal outcomes in a Brazilian cohort used to establish a tool for the early prediction of COVID-19-associated death after kidney transplantation [ 26 ], and immunosenescence likely played a role in both observations [ 27 ]. Beyond patient age, the intensity of early immunosuppression with high rates of triple immunosuppression, higher MPA exposure, higher CNI trough levels, and various induction regimens with monoclonal or polyclonal antibodies (data not shown) favored non-response to vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Even higher fatality rates were observed in kidney transplant recipients, probably because of their impaired immune response because of the long-term use of immunosuppressive drugs, in addition to the high prevalence of comorbidities such as diabetes and cardiovascular diseases. 3,4…”
mentioning
confidence: 99%
“…In a cohort study, the risk of death among liver transplant recipients was 4-fold higher in those using mycophenolate. 30 Another cohort recently published by our group showed that mTORi (versus MPA or AZA) was protective for death within 30 d. 22 Some clinical trials evaluating the effect of mTORi on COVID-19 are ongoing. Interestingly, other mTOR inhibitors beyond sirolimus and everolimus have been considered promising for inhibiting COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Nevertheless, in our previous preliminary analysis, although the use of MPA was associated with increased risk, the use of mTORi was associated with reduced risk of COVID-19–associated death. 22 Thus far, data on the impact of immunosuppressive regimens on COVID-19–clinical outcomes are lacking. Therefore, the present study seeks to compare COVID-19–associated outcomes among KTRs receiving calcineurin inhibitor (Cni) in combination with AZA, MPA, or mTORi.…”
Section: Introductionmentioning
confidence: 99%